Scale-aware stereo direct visual odometry with online photometric calibration for agricultural environment. (19th March 2023) - Yu, Tao; Yu, Xiaohan; Liu, WenLi; Xiong, Shengwu
Abstract : Vision-based localization and mapping for agricultural environment is challenging due to unstructured scene with less distinguishable landmarks and more repetitive textures, scale drift caused by wide and distant view, illumination variations and abrupt movements. To address these challenges, we propose a scale-aware stereo direct odometry with online photometric calibration for agricultural environment. We first propose a scale-aware stereo direct image alignment method to explicitly capture the scale at tracking stage. Then we optimize the scale and affine brightness parameters of stereo frames to keep the scale consistency in the sliding window. Furthermore, we incorporate online photometric calibration to resist illumination changes and exposure differences of image sequence. The proposed system achieves new state-of-the-art results on two public agricultural datasets, demonstrating its effectiveness in challenging agricultural environments. GRAPHICAL ABSTRACT: UF0001